Regional Digital Citizenship Caused by Conflict: Building Identity in the Seablings–Knetz Conflict in the Asean Digital Public - Tri Widuri, Rachma; Eva Kalyana, Layla; Nur Hidayat, Muhammad (Syntax Corporation, 2026)
While digital citizenship has traditionally been framed within national boundaries, it has been overlooked that digital interaction fosters a sense of transnational belonging. In this study, we will introduce the concept of regional digital citizenship (RDC) so that digital communication that has created conflict can encourage the emergence of regional identities that transcend the nation. This study aims to develop the concept of RDC and explore how conflict-based digital interactions shape regional identities through cross-border engagement. It uses the SEAblings–KNetz conflict on Twitter (X) and Threads as a case study. A qualitative event-based case study was used to analyze a 72-hour peak escalation period with intensive interaction between users in Southeast Asia. This study examines the processes involved using social identity theory, network identity perspectives, and emotional public theory. The analysis identified four sequential mechanisms: activation of identity superiority, boundary building, cross-border network alignment, and emotional reinforcement. These processes have built a shared digital identity in Southeast Asia that goes beyond countries. This study shows that a sense of belonging to the community emerges through bottom-up communication practices rather than institutional frameworks. By reconceptualizing digital citizenship as discursively executed and conflict-driven, this study expands the theory of digital citizenship beyond the state model and provides an analytical framework for studying the formation of supranational identities in digitally mediated contexts. The RDC will provide a foundation for future research on cross-border solidarity and regional identity building in the global digital publics.